How to Solve the Problem of Bad Performance of Cooperative Protocols at Low SNR. (21st October 2007) - Hucher Hucher, Charlotte Charlotte; Othman Othman, Ghaya Rekaya-Ben Ghaya Rekaya-Ben; Belfiore Belfiore, Jean-Claude Jean-Claude
Abstract : We propose some new adaptive amplify-and-forward (AF) and decode-and-forward (DF) protocols using a selection. The new selection criterion is a function of the instantaneous capacities of all possible transmission schemes (with or without cooperation). Outage probabilities and simulation results show that the adaptive cooperation protocols solve the problem of bad performance of cooperation protocols at low SNR. Moreover, they improve the asymptotic performance of their corresponding AF and DF protocols.